Evaluating the Effectiveness of a Blended Learning-Based Teacher Training Model in Improving the Pedagogical Competence of Senior High School Teachers - Yuliarti Effendy; Sudarwan Danim; Asti Putri Kartiwi (GHAITSA : Islamic Education Journal, 2025)
This study aims to evaluate the effectiveness of a blended learning-based teacher training model in improving the pedagogical competence of senior high school teachers. The study was motivated by the limited availability of sustainable professional development programs that effectively integrate technology into teaching practices. This research employed a quantitative approach using a pre-experimental design with a one-group pretest-posttest model. The participants consisted of 36 senior high school teachers from four schools in Ogan Komering Ilir Regency, South Sumatra. Data were collected using a pedagogical competence questionnaire administered before and after the training program. Instrument validity was examined through expert judgment, and reliability testing was conducted using Cronbach's Alpha. Data were analyzed using descriptive statistics and a paired sample t-test. The results indicate that the blended learning-based training model significantly improves teachers' pedagogical competence, particularly in lesson planning, technology integration, and the development of interactive learning media. The findings suggest that blended learning-based training can serve as an effective strategy for sustainable teacher professional development in the digital era. This study contributes to the development of technology-based teacher training models that support the improvement of pedagogical competence in secondary education. Keywords: teacher training, blended learning, pedagogical competence, professional development